Helping new executives to hit the ground running: An interview with Mark Byford, Joint Head of Global Integration Practice, Egon Zehnder. Issue 4 (27th May 2014) - Bell, Gareth
Abstract : Purpose: – The purpose of this paper is to provide an interview with Mark Byford. Design/methodology/approach: – This study discusses findings from a global survey of 500 executives about how well their needs are met by organizations. Findings: – This study outlines the importance of providing support for both external and internal hires so that they may integrate into their new roles as quickly as possible. Practical implications: – This study provides insight for human resource and learning and development professionals on how to ensure that new hires receive the support they need to adapt quickly to a new role or working environment.